Visible light-active nano-sized Fe-doped TiO2 photocatalysts and their characterization - Wetchakun N. (2014)
Nano-sized Fe-doped TiO2 samples with different amounts of iron dopant (1.0-10.0 at.%) were synthesized from titanium tetraisopropoxide (TTIP) in absolute ethanol by the modified sol-gel method. The precursor of the iron nitrate (Fe(NO3)3·9H2O) to be doped was added to an alcoholic solution containing TTIP. This solution was loaded into a pouch type cellophane membrane and placed in a clear solution containing 1:1 (v/v) ratio of absolute ethanol and distilled water with 0.5-1.0% concentrated ammonia solution for 1h. After the completion of the dialysis process (1h), the suspension was centrifuged (7500 rpm, 10 min), washed with milli-Q water and then dried in an oven at 60°C for 24h. The powder was finally calcined in a furnace at a temperature of 400°C for 3h. The use of cellophane membrane offered the advantage of a well-controlled diffusion rate. Phase composition, crystallinity, crystal size and morphology of nano-sized Fe-doped TiO 2 were examined by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on nano-sized Fe-doped TiO2. The elemental composition and oxidation state of elements were investigated by X-ray photoelectron spectroscopy (XPS). The crystalline size of 2.0 at.% of Fe-doped TiO2 was found to be in the range of 15-20 nm with BET specific surface area of 109 m2/g. UV-Vis absorption studies showed significantly enhanced red-shift in UV-Vis absorption spectra with an increased amount of iron. The complexation of Fe-oxalate was determined by using Fourier transform infrared spectrophotometry (FT-IR). The photocatalytic activity of nano-sized Fe-doped TiO2 was examined by studying the mineralization of oxalic acid under visible light irradiation. It was found that 2.0 at.% of Fe-doped TiO2 showed the highest activity. All nano-sized Fe-doped TiO2 showed higher activity than Degussa P25 and bare TiO 2. © 2008 IEEE.